Speech-language pathologists' contribution to the assessment of decision-making capacity in aphasia: A survey of common practices. (June 2014) - Aldous, Kerryn; Tolmie, Rhiannon; Worrall, Linda; Ferguson, Alison
Abstract: Speech-language pathologists' scope of practice is currently unclear in relation to their contribution to the multi-disciplinary assessment of decision-making capacity for clients with aphasia and related neurogenic communication disorders. The primary aim of the current research study was to investigate the common practices of speech-language pathologists involved in assessments of decision-making capacity. The study was completed through the use of an online survey. There were 51 of 59 respondents who indicated involvement in evaluations of decision-making. Involvement in this kind of assessment was most commonly reported by speech-language pathologists working in inpatient acute and rehabilitation settings. Respondents reported using a variety of formal and informal assessment methods in their contributions to capacity assessment. Discussion with multidisciplinary team members was reported to have the greatest influence on their recommendations. Speech-language pathologists reported that they were dissatisfied with current protocols for capacity assessments in their workplace and indicated they would benefit from further education and training in this area. The findings of this study are discussed in light of their implications for speech-language pathology practice.